Optimizing the Nuclear Concentration Measuring System of the Cutter Suction Dredger Using MCNPX Monte Carlo Code - Mojtaba Askari; Mohsen Sharifzadeh; Ali Taheri (مجله مدل سازی در مهندسی)
Using a dredger to remove mud and garbage accumulated in the river or sea docks is a common and important process. In order to monitor the condition of sediments on the sea bed, it is necessary to use an online measurement system for the concentration of transfer slurry from the floor to the surface. The nuclear-based systems have this important and operational capability to provide the possibility of online monitoring of the passing slurry by installing it on the pipeline without causing any disruption in the transfer process. The concentration measurement system of the cutter-suction dredger uses the combination of two nuclear and non-nuclear parts to measure the fluid parameters desired by the client, such as the volumetric and mass flow rate of the two-phase fluid and its components. In using hybrid systems for this purpose, basic conditions such as online measurement capability, non-physical, chemical or environmental interference in the passing flow, compatibility with the operational conditions of temperature, pressure, humidity and vibrations in the dredging site, measurement accuracy should be met and safety principles should be considered. In this study, using Monte Carlo simulation with MCNPX code, the effect of different geometrical and dimensional parameters of output gamma ray collimator on the accuracy of measuring the concentration of passing slurry was investigated, and with the considerations related to personnel radiation safety, the final optimal mode was proposed. The decrease in the placement depth of the horizontal spring inside the beam is associated with the simultaneous maximum of gradient and count statistics. In all of the mentioned situations, the opening of the conical beam-forming aperture has a higher sensitivity and resolution compared to a rectangular one.